Performance Improvement of >10kV SiC IGBTs with Retrograde p-Well - Tiwari, Amit K.; Antoniou, M.; Lophitis, Neophytos; Perkins, Samuel; Trajkovic, T.; Udrea, F. (My University, 2019)
A p-well consisting of a retrograde doping profile is investigated for performance improvement of >10kV SiC IGBTs. The retrograde p-well, which can be realized using low-energy shallow implants, effectively addresses the punch-through, a common issue in high-voltage vertical architectures consisting of a conventional p-well with typical doping density of 1e17cm-3 and depth 1µm. The innovative approach offers an extended control over the threshold voltage. Without any punch-through, a threshold voltage in the range 6V-7V is achieved with gate-oxide thickness of 100nm. Gate oxide thickness is typically restricted to 50nm if a conventional p-well with doping density of 1e17cm-3 is utilized. We therefore propose a highly promising solution, the retrograde pwell, for the development of >10kV SiC IGBTs.
Keywords: Breakdown Voltage; High-voltage SiC IGBT; Ion-implantation; Punch-through; Retrograde p-well; Threshold voltage control